Goal-based caustics - Papas, Marios; Jarosz, Wojciech; Jakob, Wenzel; Rusinkiewicz, Szymon; Matusik, Wojciech; Weyrich, Tim (Computer Graphics Forum, 2011)
We propose a novel system for designing and manufacturing surfaces that produce desired caustic images when illuminated by a light source. Our system is based on a nonnegative image decomposition using a set of possibly overlapping anisotropic Gaussian kernels. We utilize this decomposition to construct an array of continuous surface patches, each of which focuses light onto one of the Gaussian kernels, either through refraction or reflection. We show how to derive the shape of each continuous patch and arrange them by performing a discrete assignment of patches to kernels in the desired caustic. Our decomposition provides for high fidelity reconstruction of natural images using a small collection of patches. We demonstrate our approach on a wide variety of caustic images by manufacturing physical surfaces with a small number of patches. © 2010 The Author(s).
CRIS-Team Scopus Importer:2022-07-26